2018
DOI: 10.1371/journal.pone.0194282
|View full text |Cite
|
Sign up to set email alerts
|

Detection of genomic structural variations in Guizhou indigenous pigs and the comparison with other breeds

Abstract: Genomic structural variation (SV) is noticed for the contribution to genetic diversity and phenotypic changes. Guizhou indigenous pig (GZP) has been raised for hundreds of years with many special characteristics. The present paper aimed to uncover the influence of SV on gene polymorphism and the genetic mechanisms of phenotypic traits for GZP. Eighteen GZPs were chosen for resequencing by Illumina sequencing platform. The confident SVs of GZP were called out by both programs of pindel and softSV simultaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 77 publications
(83 reference statements)
0
12
0
Order By: Relevance
“…The minipig is considered a convenient animal model for preclinical studies because they rapidly achieve sexual maturity (before the age of six months) and the duration of the spermatogenic cycle is short (i.e., 35 day) [36]. Although there are structural variations at the genome level between relatively large litter sizes (average litter size: 13 piglets) and small litter sizes (average litter size: 8 piglets) in Congjiang Xiang pigs for long-term grazing and inbreeding [37,38], the breed is clearly characterized by early sexual maturity [39,40]. According to our study, Congjiang Xiang pigs exhibit the onset of puberty at approximately 2 months [40], similar to Gottingen pigs, and earlier than Yucatan minipigs (3.6-4 months) and Yorkshire (around 6 months) [41].…”
Section: Discussionmentioning
confidence: 99%
“…The minipig is considered a convenient animal model for preclinical studies because they rapidly achieve sexual maturity (before the age of six months) and the duration of the spermatogenic cycle is short (i.e., 35 day) [36]. Although there are structural variations at the genome level between relatively large litter sizes (average litter size: 13 piglets) and small litter sizes (average litter size: 8 piglets) in Congjiang Xiang pigs for long-term grazing and inbreeding [37,38], the breed is clearly characterized by early sexual maturity [39,40]. According to our study, Congjiang Xiang pigs exhibit the onset of puberty at approximately 2 months [40], similar to Gottingen pigs, and earlier than Yucatan minipigs (3.6-4 months) and Yorkshire (around 6 months) [41].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [33] demonstrated the gene polymorphism association with the components of muscle tissue in broilers. Liu et al [34] found three insertions in AKT3 gene associated with Xiang pig fattening traits.…”
Section: Discussionmentioning
confidence: 99%
“…The national conservation farm located at Bama County of Guangxi Zhuang Autonomous Region has conserved one population, which was named as BM-cov, while one closed herd (BM-clo) and one highly inbred (BM-inb) line are kept at Guangxi University [ 4 ]. All these breeds are characterized by early sexual maturity, good disease resistance, and strong adaptability in local environments [ 4 , 5 , 6 ]. In addition, because of isolation from the outside and the long time of natural and artificial selections, inbreeding has continuously increased in these populations, and the genetic diversities are expected to decrease significantly compared with the other Chinese local pig populations [ 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%